2018
DOI: 10.1177/2235042x18814939
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the association between marginalization and multimorbidity in Ontario, Canada: A cross-sectional study

Abstract: There is growing evidence to suggest that multimorbidity is not only a consequence of aging but also other environmental risk factors such as socio-economic status and social marginalization. In this study, the prevalence of multimorbidity was examined (defined as the simultaneous occurrence of two or more chronic morbidities) by age, gender and the Ontario Marginalization index (material deprivation, residential instability, dependency and ethnic concentration). With a cross-sectional design, 2015 data on 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 19 publications
3
42
2
Order By: Relevance
“…This study found a linear relationship between increasing income and lower prevalence of multimorbidity after adjusting for other factors (Tables 2 and 4), which agrees with existing research [3,8,11,38]. How income affects multimorbidity is unclear, involving multiple potential pathways [2,9].…”
Section: Socioeconomic Status (Ses): Household Income and Household Esupporting
confidence: 89%
“…This study found a linear relationship between increasing income and lower prevalence of multimorbidity after adjusting for other factors (Tables 2 and 4), which agrees with existing research [3,8,11,38]. How income affects multimorbidity is unclear, involving multiple potential pathways [2,9].…”
Section: Socioeconomic Status (Ses): Household Income and Household Esupporting
confidence: 89%
“…Area-level socioeconomic deprivation (n=17): Studies that investigated how the socioeconomic situation of participants’ residential area was associated with multimorbidity prevalence or incidence showed fairly consistent findings. 4 22 34 35 39 42 44 46 49–51 54 55 57 63 64 67 In general, multimorbidity was higher for participants residing in areas of greater deprivation than those living in more affluent areas. Odds of multimorbidity prevalence were 42% higher for participants residing in the most vs the least deprived areas when available data were pooled (OR 1.42, 95% CI 1.41 to 1.42; figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Across the 41 studies, the number of conditions included on the pre-specified list ranged from five conditions to 146 diagnostic clusters defined using O’Halloran’s criteria for chronicity. 33 Thirty-six of 41 studies included a mix of chronic physical and mental health conditions, 4 22 34–67 while four included physical conditions only. 68–71 One study was unclear about the conditions included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residential instability re ects home security, ownership and occupancy and is comprised of indicators of living alone, proportion of adults, number of people per dwelling, proportion who are single/divorced/widowed, and the proportion who have moved in the past 5 years. Marginalization and co-morbidity have previously been associated using ICES data [25].…”
Section: Introductionmentioning
confidence: 99%